(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Modern higher education should provide individuals with the opportunity to actively enter the socio-cultural space as a competent and creative representative. At the same time, the competent level of entry of the personality of the future teacher into the space of modern culture of society is provided, on the one hand, by the level of professional training of a specialist, and on the other, by the level of general cultural development of the personality